Analysis model for permanent deformation in granular materials under the action of superheavy vehicles. (May 2021) - Pérez-González, Erdrick Leandro; Bilodeau, Jean-Pascal; Doré, Guy
Abstract: The development of plastic deformation in flexible pavements has been a topic of research for several decades. Different models are available to predict this type of distress. However, the conditions defined by high loads with different stress paths than those traditionally considered during the development of performance models may cause their application to analyze non-standard vehicles to be limiting. This work presents a predictive model of permanent deformation that reduces the limitations usually encountered during the analysis of superheavy vehicles' effect on flexible pavements. The model includes mechanistic-empirical pavement analysis concepts and combines them with shakedown theory principles to identify the deformation states and associated deformation rate. The model was developed from cyclic triaxial tests and offered an analytical tool to define the boundary state of the granular materials and estimate the expected range of deformation during the passage of a superheavy vehicle over the pavement.